AN OVERVIEW OF REFRACTIVE ERRORS AMONG CHILDREN IN KOTA SOE DISTRICT, INDONESIA - Willy Yahya; Maria Larasati Susyono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Refractive error is one of the most common preventable causes of blindness in the world. Screen time and outdoor time are known as risk factors for its prevention. This study aims is to show the prevalence of children's refractive error and the difference between screen time and outdoor time. Methods: This study used a cross-sectional design to examine children's refractive error from 10 to 14 years old at five child development centers located across SoE from March 2020 to August 2021. Screen time and outdoor time data were obtained using a questionnaire, grouped into low-medium and high groups, and analyzed the differences between groups. Result: In this study, there are 429 participants with an average age of 12.65 ± 1.44 years old. The prevalence of refractive error is 9.56% and the most common error is mild myopia (43.59%). Refractive error in females is more common than in males (75.61%) and distributed in all age groups. There is no significant difference between refractive error prevalence and the amount of screen time (t 0.500; p: 0.480) and outdoor time (t: 0.944; p: 0.331). Conclusion: The most common refractive error in this study is mild myopia. There is no refractive error prevalence difference in screen time and outdoor time.